Suspected Suicide Attempt and Intentional Misuse Cases Aged 50+ Involving Amphetamine or Methylphenidate and Medical Outcomes: Associations with Co-Used Other Substances - Namkee G. Choi; Bryan Y. Choi; S. David Baker (MDPI AG, 2023)
Introduction: Given the increasing adult use of amphetamine and methylphenidate and their high misuse potential, we examined suspected suicide attempts and other intentional misuse and medical outcomes and their associations with co-used other substances among amphetamine and methylphenidate exposure cases aged 50+. Methods: Using the 2015-2021 U.S. National Poison Data System (N = 7701 amphetamine and/or methylphenidate cases), we fit two generalized linear models for a Poisson distribution with a log link function, with suspected suicide attempt versus intentional misuse and major medical effect/death versus other outcomes as the dependent variables. Results: Of all amphetamine/methylphenidate exposure cases, suspected suicide attempts and intentional misuse were 28.4% and 13.2%, respectively. Benzodiazepine use was associated with a higher likelihood, but any illicit drug use was associated with a lower likelihood of suspected suicide attempts compared to intentional misuse. The type of stimulant involved (amphetamine or methylphenidate) was not significant. The co-use of antidepressants (IRR = 1.43, 95% CI = 1.16-1.76), prescription opioids (IRR = 1.48, 95% CI = 1.21-1.81), drugs for cardiovascular disease (IRR = 1.51, 95% CI = 1.20-1.90), antipsychotics (IRR = 1.26, 95% CI = 1.02-1.55), or illicit drugs (IRR = 2.40, 95% CI = 1.82-3.15) was associated with a higher likelihood of major effect/death. Conclusions: Suspected suicide attempts or intentional misuse accounted for more than 40% of amphetamine or methylphenidate exposure cases aged 50+. The higher likelihood of major effect/death in cases involving antidepressants, antipsychotics, and cardiovascular disease drugs also suggests the confounding effects of comorbid mental and physical health problems. Careful monitoring of those who were prescribed amphetamine or methylphenidate and use other substances is needed.